ANALISIS GERAK BINTIK MATAHARI BIPOLAR SEBELUM TERJADI FLARE PADA NOAA 0484 TANGGAL 21 DAN 22 OKTOBER 2003 - Rasdewita Kesumaningrum; Clara Y. Yatini; Santi Sulistiana (Jurnal Sains Dirgantara, 2007)
In this reserach we analyzed the proper motion of individual sunspots whithin sunspots group NOAA 0484 in association with M2,4 and M1,7 flires occured on 21 October 2003 and 22 october 2003, respectively, using TRACE data (http://vestige.Imsal.com/TRACE). We measured the the movements of pairs of sunspots associated with flares relative to a reference spot in the active region whithin the period of 2 hours before the flare occurred and we calculated the mean velocities. We also measured the movements of other spots those were not associated with flares for comparisons. From these measurements and calculations, we found that (1) the distance between spots associated with flares are getting bigger especially in solar longitudinal direction and (2) they have bigger velocity that the other spots those were not associated to flares.